2013
DOI: 10.5089/9781484307373.006
|View full text |Cite
|
Sign up to set email alerts
|

Toward A Fiscal Union for the Euro Area

Abstract: Risk sharing within a common currency area. Crosscountry risk sharing arrangements take on added importance in a common currency area. Within a currency union, countries cannot use monetary policy to respond to country-specific shocks, since the common monetary policy reflects the (weighted) fundamentals of all of the members and not that of any one country. Likewise, wage and price rigidities and limited labor mobility across countries, whether due to legal constraints like the immobility of pension benefits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 9 publications
1
46
0
2
Order By: Relevance
“…Supported by back-of-the envelope-calculations, some proponents of a stabilisation fund for the euro area propose a common fund of about 1-2 % of euro area GDP (see e.g. Wolff, 2012;Trésor, 2013;Allard et al, 2013). Allard et al (ibid.…”
Section: Revenue Generating Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Supported by back-of-the envelope-calculations, some proponents of a stabilisation fund for the euro area propose a common fund of about 1-2 % of euro area GDP (see e.g. Wolff, 2012;Trésor, 2013;Allard et al, 2013). Allard et al (ibid.…”
Section: Revenue Generating Potentialmentioning
confidence: 99%
“…On behalf of the International Monetary Fund a staff discussion note (Allard et al, 2013) has identified four essential "minimal elements for a fiscal union" in order to enhance the resilience of the monetary union against future crises: first, better oversight and incentives conducive to prudent fiscal policy making at the national level are called for, basically requiring a thorough and systematic application of the European fiscal governance reforms taken in the course of the crisis. Next, some degree of centralised fiscal risk-sharing and public goods provision is advocated conditional on a framework providing better oversight and incentives.…”
Section: A Chronology Of Leading Contributionsmentioning
confidence: 99%
“…Despite recent progress with the banking and capital markets unions, financial intermediation in Europe is primarily bank based and financial markets remain fragmented along national lines. As a result of this fragmentation, the level of private risk-sharing compared to federations like the United States, Canada or Germany tends to be considerably lower and biased towards domestic credit, rather than capital flows (Allard et al, 2013). Moreover, the risk sharing through the bank lending channel tends to break down in period of crisis, exactly when needed the most (Furceri and Zdzienicka, 2015).…”
mentioning
confidence: 99%
“…Furthermore, the current system of European fiscal rules does not provide strong incentives to cut deficits or, as in case of Ireland and Spain, to sustain large surpluses in good times (Dullien, 2017). According to Allard et al (2013), with pay-outs limited to asymmetric temporary shocks to GDP, a euro area rainy-day stabilisation fund created in 1999 could have raised the overall level of income shock smoothing to 80% (roughly, the level in Germany), at the cost of annual contributions ranging from 1.5 to 2.5% of euro area GNP. Moreover, in the case of common negative shocks, the stabilisation properties of the unemployment insurance scheme may usefully be enhanced by the ability to issue debt.…”
mentioning
confidence: 99%
“…Cottarelli (2013) Allard et al (2013Allard et al ( , 2015 suggest "minimal elements for a fiscal union in the euro area" to make a future crisis less severe: (i) a better oversight of national fiscal policies and enforcement of fiscal rules, (ii) some system of temporary transfers or joint provision of common public goods or services to increase fiscal risk sharing (subject to strong oversight and enforcement of fiscal discipline), (iii) a credible pan-euro area fiscal backstop for the banking sector and (iv) common borrowing to finance greater risk sharing and a stronger backstop and the provision of a common safe asset. Corsetti et al (2014) propose "New Institutions and New Policies for a Workable Eurozone".…”
mentioning
confidence: 99%